2007
DOI: 10.1177/0093854807300757
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Arrest On Wife Assault Recidivism

Abstract: Prior research on the effect of arrest on wife assault recidivism had equivocal results and mixed reception. Arrest is not always used in wife assault cases, and several studies suggest that arrest is influenced by incident severity rather than risk of recidivism. The present study examined the effect of arrest controlling for pre-arrest actuarial risk of recidivism, which was measured retrospectively and independently of arrest decision using the Ontario Domestic Assault Risk Assessment. In an archival study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 41 publications
(63 reference statements)
3
18
0
Order By: Relevance
“…Whereas some studies have found a significant relationship between severity of violence of the arresting event and future risk of IPV (Hilton, Harris, & Rice, 2007;Kingsnorth, 2006;Miller & Krull, 1997), other studies have found this relationship to be statistically nonsignificant with trivial effect sizes. (Harrell & Smith, 1996;Miller & Krull, 1997;Murphy, Musser, & Maton, 1998;Paternoster, Bachman, Brame, & Sherman, 1997).…”
Section: Assessing Severity Of Violencementioning
confidence: 97%
“…Whereas some studies have found a significant relationship between severity of violence of the arresting event and future risk of IPV (Hilton, Harris, & Rice, 2007;Kingsnorth, 2006;Miller & Krull, 1997), other studies have found this relationship to be statistically nonsignificant with trivial effect sizes. (Harrell & Smith, 1996;Miller & Krull, 1997;Murphy, Musser, & Maton, 1998;Paternoster, Bachman, Brame, & Sherman, 1997).…”
Section: Assessing Severity Of Violencementioning
confidence: 97%
“…There is some empirical evidence providing support for the notion that the excessive levels of dependency observed in abusive men are associated with insecure attachment in childhood ( Dutton, 1995, Holtzworth-Munroe, Bates, Smutzler, & Sandin, 1997. In a recent paper examining the degree to which attachment dimensions and interpersonal problems predicted IPV posttreatment variables, it was reported that (a) pretreatment attachment anxiety and vindictive interpersonal problems predicted posttreatment mild physical abuse and psychological abuse, (b) pretreatment intrusive interpersonal problems predicted posttreatment psychological abuse, and (c) pretreatment attachment avoidance and vindictive interpersonal problems predicted posttreatment total violence severity (Lawson & Brossart, 2009).…”
Section: Attachmentmentioning
confidence: 99%
“…When police intervene, they may or may not make an arrest; if they do make an arrest, they may arrest either partner, or both partners, depending on the evidence suggestive of criminal activity. Recent studies have found little to no relationship between arrest of the male partner and reassault (e.g., Felson et al, 2005;Hilton, Harris, & Rice, 2007). This study focused on women who had experienced police intervention because they are likely to have endured severe and/or ongoing violence and because the police contact presents an opportunity to connect victims to a range of health and social services.…”
Section: Reporting To Policementioning
confidence: 99%